Circulatory Flow Restoration Versus Cardiopulmonary Resuscitation: New Therapeutic Approach in Sudden Cardiac Arrest. Issue 12 (8th September 2017) - Nour, Sayed; Carbognani, Daniel; Chachques, Juan Carlos
Abstract: Sudden cardiac arrest (SCA) remains a major problem for health authorities worldwide. Insufficiencies of current cardiopulmonary resuscitation (CPR) are most probably related to an inappropriate concept and applied methods that still concentrate on heartbeat as priority, instead of blood circulation to maintain organs' perfusions. The aim of this works is to propose a new therapeutic approach for SCA in a more effective and secure manner compared with current CPR methods. It correlates to a non‐invasive circulatory flow restoration (CFR) device composed of a multilayered thoracic and infradiaphragmatic compartments that will be pulsated alternatively and in fixed frequencies using a low‐pressure pneumatic generator. Proof‐of‐concept studies with different prototypes and methods of SCA, showed restoration of hemodynamics (BP ≥ 100 mm Hg) and increased urine output after 20 min of cardiac arrest in pediatric dogs and piglets. In summary, a CFR device can induce shear stress‐mediated endothelial function to restore microcirculation and cellular metabolism. This represents a cost‐effective method, predisposes to return of spontaneous circulation in case of SCA, adaptable for all age groups, in public and hospital environments.